Globalizing households and multi-ethnic community building in Japan - Chihiro Ishii (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
The East Asian countries are currently experiencing declining fertility rates and aging of their populations. The demographic transition is beginning to affect various societal functions, and increasing international migrants are becoming one of the responses to the transition, despite the historical reliance of these countries on their own domestic populations for economic growth through strict immigration regulations. The working-aged population in Tokyo is on the decline and companies are increasingly recruiting workers from abroad. Depopulating prefectures are welcoming more international brides into their communities. Thus, domestic demographic transition and international migration are no longer unrelated issues that can be considered independently, even in countries like Japan where the sense of ethnic homogeneity is deeply rooted. This paper uses the limited data available to illustrate some of Japan's current trends in international migration resulting from globalization and structural changes of the population. The paper then takes a more in-depth examination of Tokyo as a study case to illustrate the impacts of international migration and adaptation of communities towards a multi-ethnic society. Globalization of households is expanding the dimension of social interaction both of the Japanese and foreign residents in ways rarely seen in the past when foreign residents were largely temporary workers.
Keywords: R23; I38; J12; 330; international migration; demography; global householding; Tokyo; Japan